The Role of Academic Performance and Peer Influence in Senior High School Students' Programme Choice in Ghana (British Journal of Multidisciplinary and Advanced Studies, 2023)
The purpose of this study was to examine the determinants of students’ choice of programme at the Senior High School (SHS) level in the Gomoa East District of the Central Region of Ghana. It was a quantitative study underpinned by the positivist paradigm. The descriptive survey design was employed for the study. A self-developed questionnaire was used to collect data from a sample of 229 for the study. Multiple linear regression was used to analyse the data. The study found that students’ general academic performance was the best predictor of students’ choice of programme followed by advice from colleagues or peers of students. The study, therefore, recommended that the Ghana Education Service (GES) and Management of the Senior High Schools (SHSs), should work on equipping students with learning and research skills to enable them to enhance their self-efficacies and general academic performance.